THE INFLUENCE OF COMPANY SIZE, PROFITABILITY, AND LEVERAGE ON ACCOUNTING CONSERVATISM - Cindy Febrianti; Dian Utari; Feronika Rosalin; Echi Kurniati; Wandestarido Wandestarido (Jurnal Manajemen, 2024)
Accounting conservatism is the principle of prudence profits in financial reporting, where companies do not rush to recognize and measure assets and immediately recognize losses and debts that have the possibility of occurring. The purpose of this study is to determine the development of company size, profitability, leverage, and accounting conservatism in retail trade sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021, and also to determine the effect of company size, profitability , and leverage partially and simultaneously on accounting conservatism in retail trade sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. The sample in this study was 7 companies listed on the Indonesia Stock Exchange in 2017-2021. The data analysis used is multiple linear regression analysis techniques. The results showed that company size has a significant effect on accounting conservatism in retail trade sub-sector companies on the Indonesia Stock Exchange, while profitability and leverage variables partially have no significant effect. At least one independent variable of firm size, profitability, and leverage simultaneously affects the dependent variable of accounting conservatism. Therefore, it indicates that there is a joint influence of these variables on accounting conservatism in retail trade sub-sector companies on the Indonesia Stock Exchange.